Recent Advances in the Synthesis, Characterization, and Applications of Copper-Based Metal-Organic Frameworks (Cu-MOFs): A Comprehensive Review - Rohini R. Kadam,; Deepashree D. Kamble,; Alisha K. Khan,; Dipak S. Bhandigare,; Shamrao T. Disale,; Nandakishor S. Chandan, (International Journal of Scientific Research in Science and Technology, 2025)
Copper-based metal-organic frameworks (Cu-MOFs) have emerged as a class of highly versatile materials due to their tunable porosity, high surface area, and excellent catalytic, adsorption, and sensing capabilities. These hybrid materials, composed of copper metal centers and organic linkers, have gained significant attention for their applications in catalysis, gas storage, environmental remediation, drug delivery, and energy storage. The unique electronic properties of copper provide Cu-MOFs with distinct advantages over other metal-based MOFs, making them particularly attractive for a wide range of scientific and industrial applications. This review provides a comprehensive analysis of the recent advances in the synthesis, characterization, and applications of Cu-MOFs. Various synthesis strategies, including conventional methods such as solvothermal and hydrothermal synthesis, as well as emerging techniques like mechanochemical, microwave-assisted, and green synthesis approaches, are discussed in detail. Furthermore, post-synthetic modifications (PSM) and functionalization strategies are explored to highlight their role in enhancing Cu-MOF properties and performance. To gain a deeper understanding of their structural and functional attributes, this review outlines advanced characterization techniques, including X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA). These methods provide critical insights into the crystallinity, morphology, chemical composition, and thermal stability of Cu-MOFs. Moreover, the paper explores the diverse applications of Cu-MOFs, emphasizing their role in heterogeneous catalysis, CO₂ capture, gas separation, photocatalysis, drug delivery, biosensing, and energy conversion technologies. The challenges associated with Cu-MOFs, including stability concerns, scalability, and environmental implications, are also addressed, alongside potential future research directions aimed at overcoming these limitations. Overall, this review presents an in-depth perspective on the current state of Cu-MOF research, highlighting key advancements and future opportunities in material development and application. By integrating insights from recent studies, this work aims to serve as a valuable resource for researchers and professionals working in the field of metal-organic frameworks and related disciplines.